Predicting length of stay in patients admitted with acute upper gastrointestinal bleeding using Rockall score - Hasmoni, Mohamed Hadzri; Salleh, Rosemi (Blackwell Publishing Asia Pty Ltd, 2010)
Introduction Rockall score was originally developed to predict mortality from AUGIB. However, there have been studies advocating its use to predict endoscopic/surgical intervention and length of hospital admission. We analyzed if length of hospital stay can be predicted from the preendoscopy and/or post-endoscopy Rockall score.